ENHANCING CREATIVE THINKING SKILLS IN VISUAL ARTS FOR MIDDLE SCHOOL STUDENTS - Tog‘aev Keldiyor Xamidovich (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article investigates strategies for enhancing creative thinking skills in middle school students (grades 5–7) during visual arts lessons. The study emphasizes the importance of interactive teaching methods, problem-solving tasks, and the use of diverse artistic materials to cultivate students’ imagination, visual reasoning, and innovation. Recommendations for integrating these approaches into classroom practice are discussed, highlighting their effectiveness in developing students’ creative competencies.